Pengembangan Media Pembelajaran Anseku Berbasis Android Pada Tingkat SMP - Ratnah Lestary (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
Â This study aims to determine student and teacher assessment of learning media that have been developed by researchers. This study uses the method of analysis, design, development, implementation and evaluation. The results of student assessments of Android-based learning media in Pythagorean material, especially in the sub-section of the comparison of the sides of the triangles in the response questionnaire, obtained an average percentage of 75.9% in the appropriate category. The results of the teacher's assessment of Android media obtained an average percentage of an average of 80.3% in the feasible category.Keywords: Android, development, response, triangle, media